2015
DOI: 10.1515/intag-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental UV-A irradiation in solid-state lighting on the growth and phytochemical content of microgreens

Abstract: In this study, we sought to find and employ positive effects of UV-A irradiation on cultivation and quality of microgreens. Therefore, the goal of our study was to investigate the influence of 366, 390, and 402 nm UV-A LED wavelengths, supplemental for the basal solid-state lighting system at two UV-A irradiation levels on the growth and phytochemical contents of different microgreen plants. Depending on the species, supplemental UV-A irradiation can improve antioxidant properties of microgreens. In many cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 26 publications
7
58
0
2
Order By: Relevance
“…Similarly, basil was exhibiting a higher flavonol content when being illuminated with 13 µmol/m 2 /s at 390 nm for 7 and 14 days before harvest (Vaštakaitë et al, 2015a). Brazaitytë et al (2015) found out that supplemental 6 or 12 µmol/m 2 /s at a wavelength of 402 or 390 nm, respectively, produced best results regarding flavonol index. Exposing basil to constant 170 µmol/m 2 /s at 665 nm and adjustable intensities at 447 and 638 nm, the intensity providing best results was 50 and 80 µmol/m 2 /s, respectively (Vaštakaitë et al, 2015b).…”
Section: Flavonolsmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, basil was exhibiting a higher flavonol content when being illuminated with 13 µmol/m 2 /s at 390 nm for 7 and 14 days before harvest (Vaštakaitë et al, 2015a). Brazaitytë et al (2015) found out that supplemental 6 or 12 µmol/m 2 /s at a wavelength of 402 or 390 nm, respectively, produced best results regarding flavonol index. Exposing basil to constant 170 µmol/m 2 /s at 665 nm and adjustable intensities at 447 and 638 nm, the intensity providing best results was 50 and 80 µmol/m 2 /s, respectively (Vaštakaitë et al, 2015b).…”
Section: Flavonolsmentioning
confidence: 87%
“…In contrast to that, Vaštakaitë et al (2015a) showed that anthocyanin content in basil was highest without UV radiation. Similarly, exposing basil to three supplementary UV wavelengths at two intensities, the group of Brazaitytë et al (2015) found highest content of anthocyanins in the control group.…”
Section: Anthocyaninsmentioning
confidence: 89%
“…As such, the highest antioxidant activity and phenolic contents were recorded under predominantly red light in Valerianella locusta [ 22 ], antioxidant activity decreased with higher red ratios in coriander [ 31 ] while highest phenolic contents in tomato stems and leaves were recorded under blue light [ 61 ]. In green basil, total phenolics increased under increasing blue light ratios [ 25 ], under UV-A [ 24 ] or under red light [ 21 ]. Caffeic and rosmarinic acid are known to accumulate more in Perilla frutescens under artificial light composed 80% red and 20% blue, followed by UV-A lighting compared to natural light contained 13.5% UV-A and 23.5% blue [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of LED illumination in microgreen cultivation has been investigated in several species, such as Brassica oleracea , B. juncea , B. rapa [ 19 , 20 ], pea, broccoli, mustard, borage, amaranth, kale, beet, parsley [ 21 ], Valerianella locusta [ 22 ], buckwheat [ 23 ], Perilla frutescens [ 24 ], etc. In basil microgreens, research on light quality regarded the effect of red light supplementation on total phenolic content and antioxidant activity [ 21 ]; red, blue and far-red supplementation on antioxidant activity [ 25 ]; ultraviolet A (UV-A) supplementation on growth, phenolic, anthocyanin, ascorbate and tocopherol synthesis [ 24 ]; and blue light dosage on growth, ascorbate, total phenolic, anthocyanin, flavonoid contents and 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant activity [ 25 ]. However, all respective studies tested only a green basil cultivar, “Sweet Genovese”.…”
Section: Introductionmentioning
confidence: 99%
“…Brazaitytė et al. () found that UV‐A irradiation supplemental to basal LED illumination was generally able to improve antioxidant properties of basil, beet, and pak choi microgreens at 12.4 µmol m −2 s −1 with some wavelengths benefitting particular antioxidant components. Pak choi microgreens benefitted the most from added UV‐A irradiation, with almost all supplemental wavelengths increasing leaf area and fresh weight, DPPH free‐radical scavenging activity, total phenols, anthocyanins, total ascorbic acid, and α‐tocopherol (Brazaitytė et al., ).…”
Section: Microgreen Productionmentioning
confidence: 99%